Platería medieval en la catedral de Pamplona según un inventario de 1511 - Martínez de Aguirre, Javier (Anales de Historia del Arte, 2007)
This paper aims to present the treasurership’s inventory of Pamplona Cathedral dating to 1511, which contains interesting information about Gothic silversmith’s craft in Navarre. The document is entirely transcribed with a short remark about works typologies, similar pieces preserved in Navarre and identification of some sponsors. References concerning crosses, chalices and reliquaries are outstanding, especially because of the news relatives to some pieces with high quality and controversial chronology.